Sodobna prizadevanja v etnološkem raziskovanju prehrane - Godina-Golija, Maja (Traditiones (Ljubljana), 2000)
The paper looks at thirty years of octivities of the International Commission for Ethnological Food Research (ICEFR) and the Commission's importance for the development of research work in this area. Published papers from meetings of the commission represent important literature pertaining to specific areas of food culture. The latest conference of ICEFR took place in Slovenia in June, 2000. Ethnologists examined the role of food in yearly and local festivities and on personal holidays
Keywords: food; prehrana; ethnology; etnologija